Extreme Makeover: A Blueprint for Redefining the Role of the Liaison Librarian in the Academic Library. Issue 4 (2nd October 2017) - Ippoliti, Cinthya
ABSTRACT: Utilizing the concepts of change management and intentional change theory, this column delves into the issues facing new liaison roles and provides tips for those who are undergoing a similar process through a lens of organizational change that addresses reviewing what is working, as well as what is not, developing a clear vision and direction, breaking down the change into smaller segments, cultivating a sense of identity through shared purpose, and supporting new habits. COLUMN EDITOR'S NOTES: This column examines advances in public services internal and external to libraries. The focus is on how public services, such as instruction and education, programming, research consulting, and circulation evolve and impact users. The strength of the column is its broad, international focus and contributors are encouraged to explore issues and recent advances in public services relevant to their geographical region, as well as the larger, global audience. Interested authors are invited to submit proposals and articles to the column editor atandrea.falcone@ucdenver.edu .